The Two Faces of Deepfake: an Analysis of Contextual Thematic Exegesis - Zira Shafira (Jurnal Moderasi, 2025)
The rapid development of digital technology has significantly reshaped the way information is produced, disseminated, and consumed. Among these advancements, deepfake an AI-generated technique that produces hyper-realistic yet fabricated digital content, emerges as one of the most influential and controversial innovations in contemporary media. Its presence raises not only socio-ethical concerns but also urgent theological and moral questions within Islamic discourse. This study seeks to explore the Qur’anic perspective on deepfake by examining how the Qur'an conceptually frames human creativity, representation, deception, and accountability. Employing a qualitative, descriptive-analytical approach, this library research adopts Abdul Mustaqim’s thematic-contextual interpretation method due to its strength in connecting classical Qur’anic concepts with modern realities in a flexible yet academically grounded manner. The findings reveal that the Qur'an acknowledges two contrasting dimensions of deepfake: its constructive/beneficial dimension, including its potential as a means of knowledge (Q.S. al-‘Alaq/96:4; Q.S. al-Qalam/68:1) and its capacity to support innovation and human welfare (Q.S. Yūsuf/12:70; al-Baqarah/2:164; al-‘Ankabūt/29:43; Āl ‘Imrān/3:190-191). Conversely, the Qur'an also warns against its destructive/harmful dimension, such as major deceit and false allegations (Q.S. Yūsuf/12:18; al-Nūr/24:11-12; al-Ḥajj/22:30), as well as manipulation and unethical distortion (Q.S. al-Muṭaffifīn/83:1-3; al-Baqarah/2:9). Abstrak Perkembangan teknologi digital yang begitu pesat telah secara signifikan mengubah cara informasi diproduksi, disebarkan, dan dikonsumsi. Di antara kemajuan tersebut, deepfake adalah sebuah teknik berbasis kecerdasan buatan yang menghasilkan konten digital sangat realistis namun bersifat rekayasa yang muncul sebagai salah satu inovasi paling berpengaruh sekaligus kontroversial dalam media kontemporer. Kehadirannya tidak hanya memunculkan persoalan sosial-etis, tetapi juga pertanyaan teologis dan moral yang mendesak dalam wacana keislaman. Penelitian ini berupaya menelusuri perspektif al-Qur’an mengenai deepfake dengan mengkaji bagaimana al-Qur’an memandang kreativitas manusia, representasi, tipu daya, dan akuntabilitas. Dengan menggunakan pendekatan kualitatif deskriptif-analitis, penelitian kepustakaan ini menerapkan metode tafsir tematik-kontekstual Abdul Mustaqim karena memiliki metode kombinasi kontekstual dalam menghubungkan konsep-konsep klasik al-Qur’an dengan realitas modern secara fleksibel namun tetap akademis. Temuan penelitian menunjukkan bahwa al-Qur’an mengakui dua dimensi yang saling berlawanan dari deepfake: dimensi konstruktif/beneficial yang mencakup potensinya sebagai sarana pengetahuan (Q.S. al-‘Alaq/96:4; Q.S. al-Qalam/68:1) dan kemampuannya mendukung inovasi serta kesejahteraan manusia (Q.S. Yūsuf/12:70; al-Baqarah/2:164; al-‘Ankabūt/29:43; Āl ‘Imrān/3:190-191). Sebaliknya, al-Qur’an juga memperingatkan dimensi destruktif/harmful, seperti penipuan besar dan tuduhan palsu (Q.S. Yūsuf/12:18; al-Nūr/24:11-12; al-Ḥajj/22:30), serta manipulasi dan distorsi yang tidak etis (Q.S. al-Muṭaffifīn/83:1-3; al-Baqarah/2:9).